An Animal Model of Acute and Chronic Chagas Disease With the Reticulotropic Y Strain of Trypanosoma cruzi That Depicts the Multifunctionality and Dysfunctionality of T Cells - Mateus, Jose; Guerrero, Paula; Lasso, Paola; Cuervo, Claudia; González, John Mario; Puerta, Concepción J.; Cuéllar, Adriana (Frontiers in Immunology, 2019)
Chagas disease (ChD), a complex and persistent parasitosis caused by Trypanosoma cruzi, represents a natural model of chronic infection, in which some people exhibit cardiac or digestive complications that can result in death 20-40 years after the initial infection. Nonetheless, due to unknown mechanisms, some T. cruzi-infected individuals remain asymptomatic throughout their lives. Actually, no vaccine is available to prevent ChD, and available treatments for chronic ChD patients are controversial. Chronically T. cruzi-infected individuals exhibit a deterioration of T cell function, an exhaustion state characterized by poor cytokine production and increased inhibitory receptor coexpression, suggesting that these changes are potentially related to ChD progression. Moreover, an effective antiparasitic treatment appears to reverse this state and improve the T cell response. Taking into account these findings, the functionality state of T cells might provide a potential correlate of protection to detect individuals who will or will not develop the severe forms of ChD. Consequently, we investigated the T cell response, analyzed by flow cytometry with two multicolor immunofluorescence panels, to assess cytokines/cytotoxic molecules and the expression of inhibitory receptors, in a murine model of acute (10 and 30 days) and chronic (100 and 260 days) ChD, characterized by parasite persistence for up to 260 days postinfection and moderate inflammation of the colon and liver of T. cruzi-infected mice. Acute ChD induced a high antigen-specific multifunctional T cell response by producing IFN-, TNF-, IL-2, granzyme B, and perforin; and a high frequency of T cells coexpressed 2B4, CD160, CTLA-4, and PD-1. In contrast, chronically infected mice with moderate inflammatory infiltrate in liver tissue exhibited monofunctional antigen-specific cells, high cytotoxic activity (granzyme B and perforin), and elevated levels of inhibitory receptors (predominantly CTLA-4 and PD-1) coexpressed on T cells. Taken together, these data support our previous results showing that similar to humans, the T. cruzi persistence in mice promotes the dysfunctionality of T cells, and these changes might correlate with ChD progression. Thus, these results constitute a model that will facilitate an in-depth search for immune markers and correlates of protection, as well as long-term studies of new immunotherapy strategies for ChD.